Performance Analysis of Insulation Materials in Earthquake Resistant Buildings - Fabrio Situmorang; Rifanro Situmorang (Institute of Computer Science (IOCS), 2024)
This research investigates the performance of insulation materials in enhancing the seismic resilience of buildings against earthquake-induced forces. The study focuses on evaluating various insulation materials including fiberglass, mineral wool, and foam boards (EPS and XPS) through rigorous experimental testing under simulated seismic conditions. Findings reveal significant differences in the seismic response of insulation materials based on their damping capacities, stiffness characteristics, and resilience post-seismic event. Mineral wool demonstrates superior energy dissipation properties, effectively reducing structural vibrations and enhancing building stability. Conversely, certain foam board insulations exhibit high compressive strength, maintaining structural integrity and controlling deformations under dynamic loading conditions. The study's results align with theoretical expectations in earthquake engineering, validating the importance of material properties in enhancing building performance under seismic hazards. The implications of this research extend to informing building codes, standards, and design practices aimed at promoting sustainable and resilient urban infrastructure in earthquake-prone regions.